Protein Network Studies on PCOS Biomarkers With S100A8, Druggability Assessment, and RNA Aptamer Designing to Control Its Cyst Migration Effect - Manibalan, Subramaniyan; Shobana, Ayyachamy; Kiruthika, Manickam; Achary, Anant; Swathi, Madasamy; Venkatalakshmi, Renganathan; Thirukumaran, Kandasamy; Suhasini, K.; Roopathy, Sharon (Frontiers in Bioengineering and Biotechnology, 2020)
The Prevalence of polycystic ovary syndrome (PCOS) has been gradually increasing among adult females worldwide. Laparoscopy drilling on ovary is the only available temporary solution with a high incidence of reoccurrence. S100A8 with S100A9 complex is believed to facilitate the cyst migration in PCOS condition. The high evident protein interaction network studies between PCOS biomarkers, cancer invasion markers and the interactors of S100A8 confirm that this protein has strong interaction with other selective PCOS biomarkers, which may be associative in the immature cyst invasion process. Through the Network studies, intensive structural and pathway analysis, S100A8 is identified as a targetable protein. In this research, the Non- SELEX insilico method is adapted to construct RNA Library based on the consensus DNA sequence of Glucocorticoid Response Element (GRE) and screened the best nucleotide fragments which are bind within the active sites of the target protein. Selected sequences are joined as a single strand and screened the one which competitively binds with minimal energy. Invitro follow-up of this computational research, the designed RNA aptamer was used to infect the MCF7 cell line through Lipofectamine 2000 mediated delivery to study the anti-cell migration effect. Wound scrap assay confirms that the synthesized 18mer oligo has significant inhibition activity towards tumor cell migration at the cellular level.